DETERMINING FACTORS OF STUDENT'S ENTREPRENEURIAL INTENTION IN INDONESIA: A META-ANALYSIS - Bernardus, Denny; Murwani, Fulgentius Danardana; Satrya, Dewa Gde; Aji, Imanuel Deny Krisna (Universitas Brawijaya, Indonesia, 2019)
This study aims to conduct a meta-analysison determining factors that affect student's entrepreneurial intention. There are a variety of findings from several studies on the influence of the variables on entrepreneurial intention (Zhao et al., 2010; Bae et al., 2014). According to Wolf (1986), there is a need for synthesis on the various findings of several studies by using a meta-analysis approach.The meta-analysis procedure adopts the procedure by Baeet al.(2014), which includes sample identification for meta-analysis, determination, and measurement on the analyzed variables, and data analysis.This procedure has been able to filter samples from twelve dissertations/theses that place entrepreneurial intention as the critical variables in the studies. This procedure has also been able to determine eight predictors of entrepreneurial intention, which includesperceived desirability, entrepreneurship education, perceived feasibility, entrepreneurial self-efficacy, entrepreneurial attitude, internal locus of control, need for achievement, and adversityquotient. The meta-analysis findings show six significant predictors, which are perceived desirability, perceived feasibility, entrepreneurial self-efficacy, entrepreneurial attitude, need for achievement, and adversityquotient. Besides that, entrepreneurship education and internal locus of controlare two insignificant predictors.